Pemodelan Strategi Bisnis Desa Wisata Hanjeli Sukabumi Melalui Kerangka Business Model Canvas - Putri, Andiani Aulia; Djuwendah, Endah; Noor, Trisna Insan; Ernah, Ernah (Universitas Galuh, 2025)
Local commodity-based tourism villages have the potential to support sustainable tourism by integrating economic value, cultural heritage, and community empowerment. However, many still lack a well-structured business model. This study aims to describe the business model of the Hanjeli Tourism Village in Sukabumi Regency using the Business Model Canvas (BMC) approach. This village promotes hanjeli (Coix lacryma-jobi) as its main attraction through a community-based educational tourism concept. The method used is descriptive qualitative, with data collected through interviews, observation, and documentation. The results show that the tourism village has diverse customer segments, a unique value proposition in the form of hanjeli education and cultural preservation, and utilizes promotional channels such as social media and tourism exhibitions. The village generates revenue from various sources, including educational tourism packages, processed hanjeli products, homestay services, and donation support. Its key resources include the local community, hanjeli crops, and village infrastructure. Key activities involve education, cultivation, product processing, and promotion, supported by partnerships with government institutions, academics, and community groups. This study contributes by demonstrating how the BMC approach can be used to design an integrated business model for tourism villages based on local potential and can serve as a reference for similar tourism village development in other regions.